2018
DOI: 10.1109/trpms.2017.2765316
|View full text |Cite
|
Sign up to set email alerts
|

Maximum-Likelihood Estimation of Scintillation Pulse Timing

Abstract: Including time-of-flight information in positron emission tomography (PET) reconstruction increases the signal-to-noise ratio if the timing information is sufficiently accurate. We estimate timing information by analyzing sampled waveforms, where the sampling frequency and number of samples acquired affect the accuracy of timing estimation. An efficient data-acquisition system acquires the minimum number of samples that contains the most timing information for a desired resolution. We describe a maximum-likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Spatial patterns along the third pair of canonical variates reflected the progressive loss of dopaminergic function in the less affected striatum for both DTBZ and MP. This is consistent with previous findings (Klyuzhin et al, 2018b; Nandhagopal et al, 2009) which indicate that even though dopaminergic tracer uptake in the more affected striatum may be more sensitive for disease discrimination, tracer uptake in the less affected striatum provides a better marker to track disease progression. The inclusion of extrastriatal regions into the pattern analysis increased the pattern's correlation strengths with disease durations for both tracers compared to using the striatal regions alone; this indicates that dopaminergic denervation in other regions is also affected by disease progression in spite of the fact that the regional loadings in extrastriatal regions were by themselves not significant.…”
Section: Discussionsupporting
confidence: 93%
“…Spatial patterns along the third pair of canonical variates reflected the progressive loss of dopaminergic function in the less affected striatum for both DTBZ and MP. This is consistent with previous findings (Klyuzhin et al, 2018b; Nandhagopal et al, 2009) which indicate that even though dopaminergic tracer uptake in the more affected striatum may be more sensitive for disease discrimination, tracer uptake in the less affected striatum provides a better marker to track disease progression. The inclusion of extrastriatal regions into the pattern analysis increased the pattern's correlation strengths with disease durations for both tracers compared to using the striatal regions alone; this indicates that dopaminergic denervation in other regions is also affected by disease progression in spite of the fact that the regional loadings in extrastriatal regions were by themselves not significant.…”
Section: Discussionsupporting
confidence: 93%
“… 43 Moreover, Janigro and colleagues 44 demonstrated that the treatment of neoplasms by coupling chemotherapy and electric stimulation improved the therapeutic efficiency, allowing dose reduction of chemotherapy drugs by inhibiting multidrug resistance pumps (MDR pumps). Vijayarangan and colleagues 45 concluded that the increased delivery efficiency of the molecule was related to the membrane permeability resulting from the combined action of the RONS and the electric field. The delay between each pulse of the electric field plays a key role in the permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction location and energy combination (x,ŷ,Ê) estimated by the ML algorithm is the one that maximizes this likelihood. Details of ML estimation can be found in [9], [26], [27], and [32].…”
Section: Position and Energy Estimationmentioning
confidence: 99%